Implementasi Pendidikan Karakter Mahasiswa Melalui Pembelajaran Pancasila - Rahman, Muhammad Hadiatur; Sulianti, Ani; Isyuniandri, Dzaky (Jurnal Civic Hukum, 2024)
Student character education in the era of globalization and digitalization today has experienced a crisis, because character education when focused only on general mathematics it is a concern because it is proved by many student behavior that deviates such as online gambling, online prostitution, fraud, online loans, etc. Students have an important role in the structure of society, as agents of change and agents of future. The main objective of this study is to study the implementation of student character education through Pancasila learning in current colleges, identify the challenges and obstacles faced, and be able to propose strategies to implement them. The type of research is descriptive research with an approach to the study of literature. With measures of data collection/studies of libraries, analysis and conclusion and advice.  The results of this research find an effective strategy on how to cultivate Pancasila education in shaping the character of students through the implementation of the tri dharma of the college that must be run by all civitas that exist at the college.